2022
DOI: 10.1111/spc3.12658
|View full text |Cite
|
Sign up to set email alerts
|

How lay theories of prejudice shape prejudice confrontations: Examining beliefs about prejudice prevalence, origins, and controllability

Abstract: The formative framework in prejudice confrontations research has focused on the utility of confrontations to activate one's self-regulation strategies to interrupt unintentional prejudice, discrimination, and stereotyping. As this framework remains dominant in the literature, little research has examined everyday people's theories about prejudice that diverge from this framework and accounted for these theories in investigating confrontation rates and outcomes.In this paper, we review key lay theories of preju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…What does differentiating weight from other demography-based research on the basis of controllability mean for weight-based mistreatment? Broadly, we, as humans, stigmatize more harshly what we feel people can control (Chaney & Wedell, 2022; Rodin et al, 1989; Zhang et al, 2020), meaning that stigmatization of fatter employees is likely more sticky and more resistant to change than stigmatization of other demographic characteristics—such as those described above—assumed to be less controllable. Without clear, unequivocal evidence, pervasive culture norms about a fatter person’s lack of control over their own body appears inevitable.…”
Section: Controllability Of Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…What does differentiating weight from other demography-based research on the basis of controllability mean for weight-based mistreatment? Broadly, we, as humans, stigmatize more harshly what we feel people can control (Chaney & Wedell, 2022; Rodin et al, 1989; Zhang et al, 2020), meaning that stigmatization of fatter employees is likely more sticky and more resistant to change than stigmatization of other demographic characteristics—such as those described above—assumed to be less controllable. Without clear, unequivocal evidence, pervasive culture norms about a fatter person’s lack of control over their own body appears inevitable.…”
Section: Controllability Of Weightmentioning
confidence: 99%
“…Neurobiological research found that observers are less sensitive and reactive to the pain of fatter people when they think that the fatter person deserves censure for their unacceptable size (Azevedo et al, 2014). Our models, then, should account for both the motivation on the part of the observer to punish “deserving” fatter people and the potential for the observer to be less sensitive—or even aware—that they are punishing a fat person, meaning they are effectively ignorant of their own prejudice (Chaney & Wedell, 2022).…”
Section: Deservedness Of Mistreatmentmentioning
confidence: 99%
“…Integrating past research on prejudice confrontation and lay theories of prejudice (Chaney & Wedell, 2022; Neel & Lassetter, 2015; Rattan & Dweck, 2010), the present research examined how the age of a perpetrator of anti-Black racism would impact prejudice confrontation intentions. Across four studies ( N = 1,573), we tested our primary hypothesis that people would view an older adult perpetrator as less malleable, leading to lower perceived benefits of confronting them, and ultimately lower confrontation intentions.…”
Section: Current Researchmentioning
confidence: 99%
“…Another major cause of the inert knowledge problem is a lack of motivation to apply knowledge beyond the context of training. To address this, designers of diversity training curricula should consider how their framing of bias affects diversity-related motivations (Chaney & Wedell, 2022). For instance, framing bias as malleable (rather than fixed) can motivate equitable behavior (Neel & Shapiro, 2012).…”
Section: Educational Goals and Contentmentioning
confidence: 99%